Implementation of Game Based Learning in Biology Learning to Improve the Ability of High School Students: A Narrative Literature Review - Nida Zahra Al Banna; Agung Wijaya Subiantoro (Bioedukasi: Jurnal Pendidikan Biologi, 2025)
Game-based learning is a widely implemented model in biology education. This study aimed to know (1) the contribution of improving the ability of high school students after the implementation of Game-Based Learning in biology learning; (2) the types of Game-Based Learning implementation used in biology learning to improve the ability of high school students. This study used a narrative literature review to synthesize findings flexibly across diverse game-based learning models. Sixteen articles were selected from those published in the last 10 years (2014-2024). The research articles were obtained from Google Scholar, Scopus, and Garba Rujukan Digital (Garuda) databases. The analysis and narrative review results showed that implementing game-based learning in biology learning positively contributed to improving high school students’ ability in terms of critical thinking, activeness, independence, concept understanding, and cognitive learning outcomes. The form of implementing game-based learning in biology learning is highly varied, including web-based games (Kahoot, Quizziz, and Wordwall), android-based games, and traditional games (crossword and Snakes and Ladders). The findings provide actionable recommendations for biology educators to adopt game-based models tailored to student needs.